Wisatawan Muda dan Destinasi Wisata: Sebuah Kajian Kuantitatif - Rini Hudiono (Dinasti Review, 2024)
Tourist destinations are now more visited by groups of young tourists (under 35 years old) who are still healthy and physically strong. Several elements influence a person to do tourist destinations, namely low costs, distance and travel time, ease of access to tourist attractions, facilities, and infrastructure, the attractiveness of tourist attractions, and several other elements. This study aims to determine the factors of young people that affect the tendency to travel. The sampling technique is non-probability sampling using multiple linear regression analysis. Based on the results of research and discussions that have been reviewed previously, it can be concluded that cost, time and distance traveled, natural attractions, shopping options, and education have a significant effect on the tendency of young people under the age of 34 to visit.